Low gossypol cotton seed meal (Gossypium barbadense l.) in Holstein calf feeding - Reyes O., Jorge E.M. (2018)
The effect of three levels of inclusion of cotton seed meal (PA) of low level of gossypol in the concentrate of 36 replacement Holstein calves was evaluated. Three treatments were used: T0: 0% PA; T1: 10% PA and T2: 20% PA with 0, 150 and 300 ppm of free gossypol respectively. The diets were supplied from birth to weaning (60 days). No significant differences were observed between treatments for feed consumption, body weight gain, final body weight or size. On the contrary, the activity of the serum sorbitol dehydrogenase enzyme was 29.5, 44.7 and 59.5 U/l for T0, T1 and T2, respectively (p<0.001), exceeding the value considered normal (14.7 ± 1.3 U/l); however, there were no visible negative effects on calves.